Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1126/science.942798
|View full text |Cite
|
Sign up to set email alerts
|

Metaphase Chromosome Anomaly: Association with Drug Resistance and Cell-Specific Products

Abstract: Large, homogeneously staining chromosome regions which lack the longitudinal differentiation ordinarily revealed by cytogenetic "banding" methods have been found in antifolate-resistant Chinese hamster cells and also in human neuroblastoma cells established in vitro. The drug-resistant cells are characterized by excessive production of the target enzyme, dihydrofolate reducatase, while the human neuroblastoma cells have phenotypes of normal neuronal cells. The homogeneously staining region appears to represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
1
1

Year Published

1977
1977
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 386 publications
(126 citation statements)
references
References 8 publications
2
122
1
1
Order By: Relevance
“…A number of human tumors (1)(2)(3), in particular neuroblastomas (4)(5)(6), exhibit homogeneously staining chromosomal regions (HSRs) and extrachromosomal double minute objects (DMs) which are probably cytological manifestations of amplified genes (see ref. 7 for a review).…”
mentioning
confidence: 99%
“…A number of human tumors (1)(2)(3), in particular neuroblastomas (4)(5)(6), exhibit homogeneously staining chromosomal regions (HSRs) and extrachromosomal double minute objects (DMs) which are probably cytological manifestations of amplified genes (see ref. 7 for a review).…”
mentioning
confidence: 99%
“…The cytogenetic analysis of the 17 cell cultures derived from the tumors showed that about one-third of the tumor lines exhibited sizeable chromosome regions with a stereotype, light staining, usually referred to as HSR (homogeneously staining regions) and indicative of increased copy numbers of chromatin segments (`gene ampli®cation'; Biedler and Spengler, 1976;Levan et al, 1976;Nunberg et al, 1978). Information about ampli®cation, the location of the HSR regions, and other characteristic cytogenetic aberrations is given in Table 1.…”
Section: Cytogenetic Analysis and Cgh-analysis Of The Lb32t Tumormentioning
confidence: 99%
“…Lan-1 and Lan-6 were obtained from Dr Seeger (Childrens Hospital Los Angeles, Los Angeles, USA). SK-N-BE(2) were obtained from Dr Biedler (Biedler and Spengler, 1976) and IMR32 were purchased from American Type Culture Collection (Rockville, MD, USA). Cells were grown in Dulbecco's modified eagle's medium (DMEM) (Irvine Scientific, Irvine, CA, USA) supplemented with 10% fetal bovine serum, glutamine and penicillin/streptomycin (GIBCO/BRL, Grand Island, NY, USA).…”
Section: Cell Culturementioning
confidence: 99%